Treatment of pararectal fistulas in Crohn’s disease using laser technologies - A. A. Kamanin; P. I. Bogdanov; Z. H. Osmanov; M. I. Zaytseva; V. G. Pozdnyakova; A. A. Vinichenko; V. P. Morozov (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE of the study was to assess the possibility of using laser technologies in the treatment of perianal Crohn’s disease.METHODS AND MATERIALS. The study included 18 patients with perianal Crohn’s disease who were treated in Surgery Department ¹ 3 of the Clinic of the Research Institute of Surgery and Emergency Medicine of Pavlov University. The study was conducted in 2 stages. The first stage consisted in placing the draining seton (ligature) in the main fistulous canal. The second stage was performed in 3 months. The seton was removed with further laser destruction of the fistulous canal. On the background of surgical treatment, the patients received conservative therapy according to the recommendations of gastroenterologists.RESULTS. Every stage of surgical treatment lasted no more than 30 minutes, under intravenous anesthesia. Intraoperative blood loss did not exceed 5 ml. Due to the absence of complications, the bed-day of each stage varied from 0 to 2 days. 3 months after surgical treatment, the examination showed the complete closure of the fistula canals. The maximum period of relapse-free course was 24 months. All patients received anti-inflammatory therapy, 63 % of patients continued to receive genetically engineered biological therapy.CONCLUSION. The use of sphincter-preserving techniques proved to be effective in patients with perianal Crohn’s disease. It improves the quality of life and reduces the risk of patients’ disablement.